Proteome variations in pancreatic stellate cells upon stimulation with proinflammatory factors* - Marzoq, Aseel J.; Giese, Nathalia; Hoheisel, Jörg D.; Alhamdani, Mohamed Saiel Saeed (The journal of biological chemistry, 2013)
Pancreatic stellate cells are key mediators in chronic pancreatitis and play a central role in the development of pancreatic fibrosis, stromal formation, and progression of pancreatic cancer. This study was aimed at investigating molecular changes at the level of the proteome that are associated with the activation of pancreatic stellate cells by proinflammatory factors, namely TNF-α, FGF2, IL6, and chemokine (C-C motif) ligand 4 (CCL4). They were added individually to cells growing in serum-free medium next to controls in medium supplemented with serum, thus containing a mixture of them all, or in serum-free medium alone. Variations were detected by means of a microarray of 810 antibodies targeting relevant proteins. All tested factors triggered increased proliferation and migration. Further analysis showed that TNF-α is the prime factor responsible for the activation of pancreatic stellate cells. CCL4 is associated with cellular neovascularization, whereas FGF2 and IL6 induction led to better cellular survival and decreased apoptotic activity of the stellate cells. The identified direct effects of individual cytokines on human pancreatic stellate cells provide new insights about their contribution to pancreatic cancer promotion. Background: Stroma formation in pancreatic cancer is controlled via the activation of pancreatic stellate cells. Results: Pancreatic stellate cells demonstrate different proteomic and functional attributes following specific stimuli. Conclusion: The proteomic feature of pancreatic stellate cells shows TNF-α as a main contributor to activation. Significance: The shift of proteomes in activated cells may help in understanding the processes of stromal formation and finding new drug targets.
Available online 4 January 2021
Gesehen am 24.06.2021